Inculcating Employability Skill Sets in Undergraduates Through Employability Embedded Courses: Students Experience Anatomisation - Yawson, David Eshun; Yamoah, Fred Amofa; Sarpong, Frederick Owusu; Abban-Ampiah, Grace (Archives of Business Research, 2020)
Embedding employability skill sets into management education is important yet the experience student stakeholder gains on employability embedded courses remains unclear. We examine undergraduate student experience of the learning outcomes of work-related employability course. The survey results suggest mode of delivery and problems encountered with the course content are factors that sum up their total experiences. The results also indicate a triad consisting of difficulty of the course content, student’s work experience and satisfaction with the course content are strongly associated in determining students’ experiences. We discuss the implications of these findings for employability embedded curriculum development theory and practice.